Enhancing wine tourism experience through developing wine tourist typology and providing complementary activities. (5th July 2022) - Fytopoulou, Eleftheria; Karasmanaki, Evangelia; Galatsidas, Spyridon; Andrea, Veronika; Tsantopoulos, Georgios
Wine tourism can flourish in rural regions which often have low levels of economic development. To establish rural regions as attractive wine destinations, it is necessary to understand what affects wine tourists' satisfaction and find ways to enhance the wine tourism product. Hence, the aim of the present study is to build a typology of wine tourists based on their satisfaction as well as to examine their preferences for complementary activities while visiting a wine destination in Northern Greece. According to the analysis, two dimensions characterised wine tourists' visit; the first involved the wine region's character and infrastructure and the second their satisfaction with the visit. Moreover, wine tourists expressed interest for carrying out complementary activities unrelated to wine while visiting the wine destination. It may be concluded that wine destinations can develop by applying strategies aiming at enhancing tourist satisfaction and by providing wine tourists with an integrated recreational experience that includes activities which fully correspond to their preferences.